Connecting with reluctant teen readers tips, titles, and tools - Jones, Patrick; Hartman, Maureen L.; Taylor, Patricia (Neal-Schuman Publ., 2006)
A practical guide to defining and attracting reluctant readers is divided into three parts: "Tips That Work," "Titles That Work," and "Tools That Work."
Includes bibliographical references (p. 265-278) and indexes
Keywords: Young adults / Books and reading / Handbooks, manuals, etc; Teenagers / Books and reading / Handbooks, manuals, etc; Young adults' libraries / Book lists; Children's libraries / Book lists; Young adults' libraries / Administration / Handbooks, manuals, etc; Young adult literature / Bibliography; Children's libraries -- Book lists; Teenagers -- Books and reading -- Handbooks, manuals, etc; Young adult literature -- Bibliography; Young adults -- Books and reading -- Handbooks, manuals, etc; Young adults' libraries -- Book lists; Young adults' libraries -- Administration -- Handbooks, manuals, etc; Jugend; Englisch; Bibliothek; Jugendliteratur; Leseförderung; Bibliografie